Rancang Bangun Sistem Pengaduan Masyarakat Berbasis Web di Kesbangpol Tebing Tinggi - Adnan Buyung Nasution; Pira Safitri; Nazli Adittra (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2025)
Information technology has become an important element in improving operational efficiency and data management in various sectors. The Tebing Tinggi Kesbangpol Office, as an agency that handles public complaint services, still faces obstacles in managing complaints that are carried out manually. This process causes delays in handling reports, lack of transparency, and difficulties for the public in monitoring the status of their complaints. This study aims to design a web-based public complaint process flow with the PIECES (Performance, Information, Economic, Control, Efficiency, and Service) approach to improve service effectiveness. This method is used to analyze various aspects of the running system and identify needed improvements. Data were obtained through observation, interviews with employees, and literature studies. From the results of the design carried out, it is expected that the complaint service process can be faster, information more transparent, and increase employee work efficiency. In addition, this design provides an overview of how the system can help the public in monitoring complaint status online and help agencies in managing data in a more structured and accountable manner. With this design, it is hoped that the Tebing Tinggi Kesbangpol can have guidelines in developing a more effective system to improve the quality of public complaint services.